Differences in berry skin and pulp cell wall polysaccharides from ripe and overripe Shiraz grapes evaluated using glycan profiling reveals extensin-rich flesh. (30th November 2021) - Gao, Yu; Fangel, Jonatan U.; Willats, William G.T.; Vivier, Melané A.; Moore, John P.
Highlights: Comprehensive Microarray Polymer Profiling was used to directly profile skins and pulp of Shiraz berries. The skin was rich in pectins and xyloglucans, the pulp tissues were mainly composed of extensin glycoproteins. Overripe berries, particularly those from the warmer region site, revealed degradation of their pectin and extensin epitopes. Abstract: Shiraz is a widely planted cultivar in many of the world's top wine regions where it is used for the production of top-quality single varietal or blended red wines. Cell wall changes during grape ripening and over-ripening have been investigated, particularly in the context of understanding berry deconstruction thereby facilitating the release of favorable compounds during winemaking. However, no information is available on cell wall changes during berry shrinkage in Shiraz. Glycan microarray technology was used to directly profile Shiraz berries for cell wall polysaccharide and glycoprotein epitopes. Skins and pulp tissues were profiled separately and revealed that whereas the skin was rich in pectins and xyloglucans, the pulp tissues were mainly composed of extensin glycoproteins. Overripe (26–28°B) berries, particularly those from the warmer region site, revealed degradation of their pectin and extensin epitopes.